Factors influencing intention to use home healthcare service in Vietnam: A study using the TAM approach - Lam, Nguyen Thanh; Tuan, Pham Van; Van, Khai Huynh (Edelweiss Applied Science and Technology, 2026)
This study investigates the key cognitive, social, and structural determinants influencing Vietnamese consumers’ behavioral intention to adopt Home Healthcare Services (HHCS), an emerging healthcare model increasingly supported by telehealth technologies. A quantitative research design was applied using an online survey distributed in major urban centers in Vietnam. Convenience sampling yielded 766 valid responses. The proposed model integrates constructs from TAM/TPB and the COM-B framework, including perceived usefulness, ease of use, reliability, social influence, capability, affordability, attitude, and behavioral intention. Structural Equation Modeling (SEM) was employed to test hypothesized relationships. Results show that perceived usefulness, ease of use, and reliability significantly enhance consumers’ attitudes toward HHCS. Financial cost and affordability emerged as the strongest predictors of adoption intention (β = 0.288), followed by social influence (β = 0.250), attitude (β = 0.190), and capability (β = 0.183). Educational level was also positively associated with intention. The findings confirm that HHCS adoption in Vietnam is driven strongly by practical affordability and collectivist social norms. Service providers and policymakers should therefore prioritize affordable pricing strategies, strengthen service trust, and leverage community influence to promote sustainable HHCS development in emerging markets.